HOUSING NEEDS FULFILMENT FOR LOW-INCOME GROUP - Anjay Kumar Mishra (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2019)
ABSTRACT There is the requirement of large number of housing units to meet the housing needs of low-income groups in Kathmandu Valley. The overall objective of this study was to find out the appropriate ways to address these needs. The questionnaire survey and interview were carried out with low-income groups, housing experts, planners, implementers, and concerned organizations. Relative Importance Index (RII) has been calculated to find out the hierarchy of important factors and appropriate approaches for addressing the housing needs for low-income groups in Kathmandu Valley. This number is very large and the location and nature of squatter settlements are different causing it is impossible that only one approach will be suitable to meet the housing needs of the entire low-income groups. Hence, different suitable approaches have been considered to address housing needs. In a city like Kathmandu where the price of land is skyrocketing, purchasing the land parcel is beyond the capacity of the low-income groups. In this approach, the rental housing at the fringe area is more suitable to fulfill the housing needs of the low-income groups, in order to provide an adequate housing facility at a reasonable cost. The monthly rent of the housing allocated for different categories of low-income groups should be positively classified based on their affordability. Keywords: Perception, Approaches, Cost Recovery, Affordability, Accessibility